Helminths of domestic and wild chicken birds (Aves: Galliformes) of Uzbekistan - F. D. Akramova; U. A. Shakarbaev; A. S. Zhangabaev; I. M. Arepbaev; S. Sh. Rabbimov; D. A. Azimov (Российский паразитологический журнал)
The purpose of the research is studying existing fauna and ecology of Galliform helminths in biogeocenoses of Uzbekistan.Materials and methods. Parasitic worms were collected from chicken-like birds of the terrestrial cenoses of Karakalpakstan and North-eastern Uzbekistan. Birds were studied in all seasons of 2018–2020. Wild birds – Himalayan hen, keklik, grey partridge, quail and pheasant, were hunted by local hunters during hunting seasons, while domestic birds - chickens, turkeys and guinea fowls were uncovered from different types of poultry farms. The study of birds was carried out by well-known methods. It was examined 913 wild and 755 domestic chicken-like animals. The detected cestodes and trematodes were fixed in 70% alcohol, and the nematodes were fixed in Barbagallo liquid. The determination of helminth species was carried out according to the well-known guidelines of domestic and foreign authors.Results and discussion. We found that helminthoses were widespread among representatives of Galliformes in Uzbekistan. Total helminth infections in domestic and wild Galliformes were 50.5%. In infected birds, 44 helminth species were identified, among which 10 species were cestodes, 12 species were trematodes and 22 species were nematodes. Helminth species diversity was the most extensive in the domestic chicken (36 species), turkey (21), and partridge (20). For the first time for the helminth fauna in Galliformes in Uzbekistan, we identified 3 trematode species – Brachylaema fuscatus, Collyriclum faba and Echinostoma miyagawai, and 10 nematode species of the genera Capillaria, Aonchotheca, Ascaridia, Heterakis, Dispharynx, Streptocara, Tetrameres, Diplotriaena and Ornithofilaria.